Analisis Perbandingan Dampak Sebelum dan Sesudah Merger Horizontal Terhadap Kinerja Keuangan Perusahaan di Indonesia Yang Terdaftar di BEI Periode 2014-2019 - Delia Saputri; Eni Kaharti (Jurnal Ilmiah Mahasiswa Manajemen, Bisnis dan Akuntansi (JIMMBA), 2022)
This study aims to compare the impact before and after horizontal mergers on Net Profit Margin (NPM), Operating Profit Margin (OPM), Debt to Assets Ratio (DAR), and Debt to Equity Ratio (DER). The population of this study are companies that have horizontally merged and are listed on the IDX for the period 2014-2019 with a total of 90 companies. By using the purposive sampling method, 8 companies that have performed horizontal mergers were taken. The analysis technique used is hypothesis testing using paired sample t test. The results of this study indicate that there is no significant comparison of the impact before and after the horizontal merger on Net Profit Margin (NPM), there is no significant comparison of the impact before and after the horizontal merger on Operating Profit Margin (OPM), there is no significant comparison. on the impact before and after the horizontal merger on the Debt to Assets Ratio (DAR), and there is a significant comparison on the impact before and after the horizontal merger on the Debt to Equity Ratio (DER).